Microbiologic yield of bronchoalveolar lavage specimens from stem cell transplant recipients. Issue 3 (12th April 2017) - Sakata, Kenneth K.; Klassen, Christine L.; Bollin, Kathryn B.; Grys, Thomas E.; Slack, James L.; Wesselius, Lewis J.; Vikram, Holenarasipur R.
Abstract: Purpose: Stem cell transplant (SCT) recipients commonly undergo bronchoalveolar lavage (BAL) collection as an infectious pulmonary work‐up. Previous studies report the utility and overall diagnostic yield of fiberoptic bronchoscopy with BAL in this vulnerable population, though none focused purely on microbiologic yield or made comparisons with less invasive means of pathogen detection. We sought to determine and elaborate on the microbiologic yield of BAL in SCT recipients, assess a correlation between BAL studies and less invasive means of pathogen detection, and assess the utility of repeating a BAL within 30 days. Methods: Between January 1, 2009, and July 31, 2013, we reviewed medical records of 125 SCT recipients who underwent 179 BALs. In addition to demographic information and details pertaining to their SCT, a comprehensive review of their microbiologic data was performed and recorded. Results: Our study showed an overall BAL microbiologic yield of 40%, despite 92% of patients receiving broad‐spectrum antimicrobial therapy at the time of the BAL procedure. Conclusions: Although an initial BAL sample in this population provides crucial microbiologic information, repeating the procedure within 30 days may have minimal additional microbiologic yield. BAL continues to be an essential diagnostic tool in SCT recipients undergoing an infectious pulmonary work‐up.